Comparison of in vitro scratch wound assay experimental procedures - Wilhelmina E. Radstake; Kiran Gautam; Cynthia Van Rompay; Randy Vermeesen; Kevin Tabury; Mieke Verslegers; Sarah Baatout; Bjorn Baselet (Biochemistry and Biophysics Reports, 2023)
Fibroblast migration is an important aspect of wound healing. Different factors can influence migration and as such proper wound healing. In vitro scratch wound assays are used to examine cellular migration. However, the wide array of techniques available reduces reproducibility of findings. In this paper, we compare two techniques for wound creation; i.e. the exclusion method or scratching of cell monolayers. Furthermore, we investigate if analysis software influences experimental outcome by comparing both commercially and freely available analysis software. Besides, we examine the effect of cortisol on migration behavior of fibroblasts and identify possible caveats in experimental design. Results show a significantly reduced migration of fibroblasts when wounds are created using a cell exclusion method. Furthermore, addition of cortisol to the cell culture media only reduced migration of fibroblast monolayers that had been scratched but not in those where wounds were created using the exclusion method. A possible explanation related to cytokine expression is discussed.